Surface Binding of Toxins and Heavy Metals by Probiotics - Zoghi, Alaleh; Khosravi-Darani, Kianoush; Sohrabvandi, Sara (Mini Reviews in Medicinal Chemistry, 2014)
Removal of toxic metals and toxins using microbial biomass has been introduced as an inexpensive, new promising method on top of conventional methods for decontamination of food, raw material and concentrated. In this article the potential application of lactic acid bacteria and yeasts as the most familiar probiotics to eliminate, inactivate or reduce bioavailability of contamination in foods and feed has been reviewed. After fast glance to beneficial health effects and preservative properties of lactic acid bacteria, the mechanisms which explain antibacterial and antifungal efficiency as well as their antifungal metabolites are mentioned. Then the article has been focused on potential application of single strain or combination of lactic acid bacteria for removal of heavy metals (copper, lead, cadmium, chromium, arsenic), cyanotoxins (microcystin-LR, -RR, -LF) and mycotoxins (aflatoxin B1, B2, B2a, M1, M2, G1, G2, patulin, ochratoxin A, deoxynivalenol, fumonisin B1 and B2, 3-acetyldeoxynivalenol, deoxynivalenol, fusarenon, nivalenol, diacetoxyscirpenol, HT-2 and T-2 toxin, zearalenone and its derivative, etc) from aqueous solutions in vitro. Wherever possible the mechanism of decontamination and the factors influencing yield of removal are discussed. Some factors which can facilitate metal removal capacity of lactic acid bacteria including the strains, surface charge, pH, temperature, presence of other cations are introduced. The cell wall structure of lactic acid bacteria and yeasts are also introduced for further explanation of mechanism of action in complex binding of probiotic to contaminants and strength of mycotoxin– bacterium interaction.
Keywords: probiotic bacteria